Strategies for Coping With Stress Used by Nurses in Poland and Belarus During the COVID-19 Pandemic - Kowalczuk, Krystyna; Shpakou, Andrei; Hermanowicz, Justyna M.; Krajewska-Kułak, Elzbieta; Sobolewski, Marek (Frontiers in Psychiatry, 2022)
Introduction Stress is an inseparable element of nurses' work. It is also the cause of wellbeing disorders and the source of various diseases. The wellbeing and health of nurses has a direct impact on the quality of care and health outcomes for patients. An appropriate stress coping strategy can reduce the impact of stress and mitigate its negative consequences. The COVID-19 pandemic, especially in its initial period, was a source of enormous additional stress for nurses. In Poland and Belarus: two neighboring countries with common history and similar culture, the authorities took a completely different approach to fighting the COVID-19 pandemic. Aim The purpose of this study was to investigate and compare how nurses in Poland and Belarus cope with stress during the COVID-19 pandemic. Materials and Method The cross-sectional study was conducted among 284 nurses working in hospital in Bialystok, Poland (158) and in Grodno, Belarus (126). Mini-Cope inventory - the polish adaptation of Carver's BriefCope was used for measuring coping with stress. Results Only 17.5% of Belarusian nurses were tested for the presence of the virus and only 4.8% were infected, while in Poland it was 50.6 and 31.0%, respectively. The most frequent used coping strategies were active strategies (active coping, planning) and the least-used were avoidance strategies (behavioral disengagement, substance use) in both countries. Polish nurses significantly more often than Belorussian used support-seeking/emotion-oriented strategies, as well as avoidance strategies. No differences were found for active coping strategies between the both groups. Contact with a patient infected with the SARS-CoV2 virus did not influence the choice of stress coping strategies by nurses in both countries. Staying in quarantine or home isolation favored more active coping strategies, especially in the case of Belarusian nurses. Taking a SARS-CoV-2 test did not statistically differentiate the choice of coping strategies in the Belarusian group. In the Polish group, nurses with a positive SARS-CoV-2 test result used both use of instrumental support and use of emotional support strategies less frequently. SARS-CoV-2 virus infection did not statistically differentiated how stressful situations were handled in Polish group. Conclusions Polish and Belorussian nurses used similar strategies to cope with stress in the face of the COVID-19 pandemic. The social and demographic differences between Polish and Belorussian nurses differentiated the choice of coping strategies among the respondents to a greater extent than the completely different approach of the media and authorities to the COVID-19 pandemic in the two countries. The threat of the COVID-19 pandemic does not affect the choice of stress coping strategies by nurses in Poland and Belarus. Being in quarantine or home isolation favored the use of active coping strategies among Belorussian nurses. Polish nurses, on the other hand, were more likely to turn to religion after being quarantined.